Economic contribution and social welfare of recreational charter boat fisheries in the northeast Atlantic: The cases of Galicia (Spain) and Madeira archipelago (Portugal) - Pita, Pablo; Ainsworth, Gillian B.; Antelo, Manel; Gouveia, Lidia; Martínez-Escauriaza, Roi; Tubío, Ana; Villasante, Sebastián (Frontiers in Marine Science, 2022)
Charter boat fishing has been little studied in temperate regions, and the factors that trigger its development and social contribution to fishing communities are unknown. We performed an economic analysis of recreational charter boat fisheries in the Eastern North Atlantic to assess their contribution to social welfare. We selected two case studies located in Galicia (NW Spain) and Madeira archipelago (Portugal). The two cases differ in the socioecological attributes in which recreational charter boat fishing is developed (e.g., relevance of commercial fishing, tourism, or targeted species), that were included in the assessment. Up to 7 charter fishing companies were identified in Galicia (10 boats) and 14 in Madeira (18 boats), and information on the costs and benefits of the activity were collected by a questionnaire answered by company managers and skippers. Charter boats go fishing for 39.3 ± 41.5 (SD) fishing journeys and take 2 500 anglers on board per year in Galicia, while in Madeira they fish 63.7 ± 32.7 journeys and take 3 200 anglers on board. The economic balance of companies was more favorable in Madeira, with an average gross annual profit of € 28 883 ± 30 755, while economic yield in Galicia was € 4 444 ± 7 916. We applied a travel cost method to assess the recreation demand of recreational fishing trips based on a questionnaire answered by 150 clients in Galicia and 55 in Madeira. We estimated the visitor surplus mean value to be € 1 385 per year in Galicia (CI95%= € 1 219 – € 1 550), and € 1 738 in Madeira (CI95%= € 1 433 – 2 043). The social annual recreation value of Galician fishery was worth € 3.4 Million, ranging between € 3.0 M and € 3.8 M, a value well below the annual economic impact generated by commercial fishing (€ 700 M). The recreation value of the charter boat fishery in Madeira, € 6.3 M, ranging between € 5.2 M and € 7.5 M, is comparable to the annual economic impact of commercial fishing, that contributes to the local economy with € 12 M